Carrots and related apiaceae crops - Geoffriau, Emmanuel; Simon, P. W. (Philipp W.) (Crop production science in horticulture ;, 2021)
"Fully updated with new content and full-colour figures, the second edition of this successful book reflects developments and growth in our knowledge of carrots and related crops. It covers the scientific basis of their biology and production, with updated technical crop management content"--